The associations of maternal serum ferritin levels with hypertensive disorders of pregnancy: a longitudinal cohort study - Mo, Huiqin; Wang, Zijun; Qu, Cuicui; Liu, Xiaohua (Frontiers in Nutrition, 2025)
BackgroundThe longitudinal fluctuations in maternal serum ferritin (SF) levels during gestation, acting as indirect indicators of iron supplementation, have not been thoroughly investigated in relation to the incidence of hypertensive disorders of pregnancy (HDP).MethodsA retrospective cohort investigation was carried out at a tertiary maternity hospital in Shanghai, involving women with serum ferritin (SF) measurements at 8.0–13.6 gestational weeks (GW) and at 29.0–31.6 GW. Logistic regression analysis was employed to evaluate the relationship between maternal SF levels, their longitudinal variations, with the risk of HDP.ResultsThe study included 17,472 women, among whom 473(2.71%) developed gestational hypertension (GH) and 560(3.21%) developed preeclampsia (PE). Adjusted odds ratios (ORs; 95% confidence intervals) for HDP across ascending quartiles of SF concentrations were as follows: at 8.0–13.6 GW, 1.00 (reference), 1.043 (0.864–1.258), 1.060 (0.878–1.279), and 1.234 (1.027–1.482); and at 29.0–31.6 GW, 1.00 (reference), 0.973 (0.800–1.181), 1.076 (0.890–1.301), and 1.299 (1.082–1.560). Women with SF levels in the highest quartile at 8.0–13.6 GW exhibited reduced HDP risk when their SF levels declined to the lowest quartile by 29.0–31.6 GW. Conversely, those with SF levels in the lowest quartile early in pregnancy but transitioning to the highest quartile later in pregnancy demonstrated a significantly elevated HDP incidence (8.2%; OR: 1.445, 95% CI: 1.003–2.081).ConclusionMaternal SF levels demonstrated an independent positive association with HDP risk during early and late gestational stages. These findings suggest that routine iron supplementation in iron-replete women may exacerbate HDP risk and warrants careful reconsideration.